Modelling of urea aggregation efficiency via particle tracking velocimetry in fluidized bed granulation - Zhalehrajabi, E. (Elsevier Ltd, 2020)
This work presents a predictive model to estimate the particle size distribution (PSD) and aggregation efficiency of wet granulation of urea in top spray fluidized bed. To elucidate the model solution, the experimental granulation process of urea particles was performed. Urea particles with an average size of 250 Âµm, were charged and fluidized at the granulator by spraying a binder solution. Urea granule samples were withdrawn at different granulation time, and the respective particle size distributions were characterized using the sieving method. An empirical model for aggregation rate constant has been developed based on the experimental data at various operating conditions and used in population balance model to estimate the PSD. Furthermore, the model has been extended to determine aggregation efficiency using particle tracking velocimetry method (PTV). The developed model could be employed to estimate the urea granulation performance and kinetics in fluidized bed for design and scale-up purpose. Â© 2020 Elsevier Ltd